A Novel Fast CT Perfusion Core-Penumbra Mismatch Score: Correlation With Stroke Outcome. Issue 2 (4th March 2021) - Pozzi-Mucelli, Roberta A.; Furlanis, Giovanni; Caruso, Paola; Lugnan, Carlo; Zdjelar, Adrian; Degrassi, Ferruccio; Bottaro, Lorella; Ukmar, Maja; Naccarato, Marcello; Manganotti, Paolo; Cova, Maria A.
Abstract : Background: Advanced neuroimaging can identify patients who can most benefit from reperfusion treatment, discriminating between ischemic core and penumbra area in a quick and accurate manner. Despite core-penumbra mismatch being an independent prognostic factor, computed tomography perfusion (CTP) assessment is still debated in hyperacute decision-making. The authors aimed to study a novel CTP mismatch score in emergency settings and to investigate its relation with clinical outcome in acute ischemic stroke patients treated with intravenous thrombolysis (IVT). Methods: Neuroimaging and clinical data of 226 consecutive acute ischemic stroke patients were analyzed. The study population was divided into 5 different CTP scores: (0) without perfusion deficit, (1) only penumbra, (2) penumbra > core, (3) core ≥ penumbra, (4) only core. For differences in outcome between treated and nontreated patients, and among CTP core-penumbra groups to be assessed, the authors have evaluated the outcome in terms of National Institutes of Health Stroke Scale (NIHSS) and modified Rankin scale (mRS) at discharge and symptomatic intracerebral hemorrhage. Results: A decrease in NIHSS was statistically greater in IVT-treated patients compared to nontreated patients showing only penumbra (ΔNIHSS%: 80.0% vs. 50.0%; P =0.0023) or no perfusion deficit (ΔNIHSS%: 89.4% vs. 61.5%; P =0.027) on CTP maps. The same trend was found in other groups without significant difference. A significant correlation was found in IVT patients between core/penumbra score and outcome in terms of ΔNIHSS (Kendall τ=−0.19; P =0.004). Conclusions: The authors proposed a novel immediate CTP assessment to score perfusion mismatch in emergency settings to guide clinicians' decision-making for aggressive treatment and to prevent stroke-related disability.